Basal chordae sites on the mitral valve determine the severity of secondary mitral regurgitation. Issue 13 (23rd March 2015) - Song, Jong-Min; Kim, Jae-Joong; Ha, Tae-Yong; Lee, Jae Won; Jung, Sung-Ho; Hwang, Il-Seon; Lee, Inchul; Sun, Byung Joo; Kim, Dae-Hee; Kang, Duk-Hyun; Song, Jae-Kwan
Abstract : Objectives: To evaluate the variation between individuals in terms of basal chordae (BC) attachment sites on the mitral valve (MV) and the influence of this variation on secondary mitral regurgitation (MR) severity. Background: BC-mediated MV tenting is the main cause of secondary MR. Methods: In this prospective cross-sectional study, 38 consecutive patients with dilated or ischaemic cardiomyopathy who were due for cardiac transplantation underwent preoperative 3D full volume/colour Doppler echocardiography in sinus rhythm, and MV apparatus geometry, LV volume and MR severity were assessed. The lengths and insertion sites of four BC in the explanted hearts were measured post-transplantation before fixation. Results: Multiple linear regression analyses revealed that the anterior leaflet systolic tenting angle and bending angle associated with the distance between the medial and lateral BC insertion sites. By contrast, the posterior leaflet tenting angle associated largely with LV volume indices. The mean longitudinal distance of the four BC from the MV edge was the main determinant of the distal length of the anterior MV from the angulation point. Square root of effective regurgitant orifice area (√EROA) only associated significantly with the mean longitudinal distance of the outer two BC from the MV edge (r=0.509, p=0.001) among pathological parameters, and the central MV tenting area (r=0.524, p=0.001) among echocardiographical parameters. √EROA did not correlate with LV volume indices, LVEF or BC lengths. Conclusions: BC insertion sites were associated with systolic anterior MV configuration and secondary MR severity in dilated LV and severe systolic dysfunction.